Clinical and Pharmacological Aspects of Resistance to Eradication Therapy of Helicobacter Pylori Infection - S. Yu. Serebrova; A. B. Prokofiev; N. N. Eremenko; M. V. Zhuravleva; T. A. Alexandrova (Антибиотики и Химиотерапия)
Despite the evidence of the effectiveness of modern medicines, which are included in modern schemes of eradication therapy, against Helicobacter pylori, the problem of growth of microorganism resistance to them is relevant not only for various regions of the Russian Federation; it also has an international and even intercontinental spread. The article presents modern information on Helicobacter pylori pathogenicity, the prevalence and development mechanisms of its resistance to antibiotics widely used for eradication, the contradictions in the information on indications, duration of use, anti-Helicobacter pylori treatment regimens and dosage in modern clinical guidelines and instructions for medical use.